Konsep Cahaya dalam Al-Qur’an: (Kajian Semantik Al-Qur’an) - Dyah Nurul Azizah (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2020)
An-Nur in the Qur’an is a familiar word. It was mentioned in many verses withdifferent context. An-Nur in each verse has a different meaning, then need to adeep understanding. The purpose of this study is to know the real meaning fromAn-Nur in the Qur’an use a semantic theory. Semantic of Al-Qur’an is an attemptto reveal the world view of Qur’an on some terms and vocabularies in Qur’anthrough a semantic analysis. The analysis process begins from research a basicmeaning and contextual meaning of An-Nur with some verses. The conclusions ofthis study is that the word Án-Nur in the Qur’an has three categories; 1) An-Nuras something to fight digression, 2) An-Nur as the religion from God, and 3) Godas An-Nur or the Highest Level of An-Nur. The word An-Nur in the Qu’an isalways mentioned in singular form, while the darkness (opposite) is alwaysmentioned in plural form. That shows there are many dark or bad things, such asa various kinds of immorality, but it will be defeated with the one of the light (An-Nur). God as the Highest Light, Eternal, True, and Everything